Synthesis of Novel Iono- and Photochromic Spiropyrans Derived from 6,7-Dihydroxy-8-Formyl-4-Methyl-2H-Chromene-2-One - Olga G. Nikolaeva; Alexey V. Tsukanov; Evgenii N. Shepelenko; Boris S. Lukyanov; Anatoly V. Metelitsa; Olga Yu. Kostyrina; Alexander D. Dubonosov; Vladimir A. Bren; Vladimir I. Minkin (International Journal of Photoenergy)
Novel photochromic spiropyrans (SPPs) containing 6′-hydroxy group were synthesized and their spectral properties as well as abilities for complexation with metal ions studied. In solutions they exist as equilibrium mixture of spirocyclic (A) and merocyanine (B) isomers. The largest content of merocyanine form was found for the derivative with an electron-donating methyl group in position 5 of hetaryl fragment. The irradiation of SPPs in acetonitrile shifts the equilibrium to the B form. Similar effect causes the addition of metal cations due to formation of colored complexes with merocyanine isomers.